1998
DOI: 10.1152/jappl.1998.85.4.1502
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine, performance, and metabolism during repeated Wingate exercise tests

Abstract: Investigations examining the ergogenic and metabolic influence of caffeine during short-term high-intensity exercise are few in number and have produced inconsistent results. This study examined the effects of caffeine on repeated bouts of high-intensity exercise in recreationally active men. Subjects (n = 9) completed four 30-s Wingate (WG) sprints with 4 min of rest between each exercise bout on two separate occasions. One hour before exercise, either placebo (P1; dextrose) or caffeine (Caf; 6 mg/kg) capsule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
165
1
11

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(202 citation statements)
references
References 25 publications
25
165
1
11
Order By: Relevance
“…The subjects in a study were male students of strength and conditioning and sport science and trained competitive male athletes; the performance task was cycle ergometer sprints, and 30 s Wingate test was conducted (Glaister et al, 2014;Woolf, Bidwell, Carlson, 2008). It seems that caffeine consumption in events that heavily rely on the glycolytic system (15 s to 3 min) has no positive impact on performance (possibly because of increase in plasma ammonia levels and decrease in intracellular pH) (Greer, McLean, Graham, 1998;Sökmen et al, 2008). Also, it is indicated that the sensitivity of caffeine consumers to the performance enhancing effects of caffeine is related to habitual intake (Woolf, Bidwell, Carlson, 2008).…”
mentioning
confidence: 99%
“…The subjects in a study were male students of strength and conditioning and sport science and trained competitive male athletes; the performance task was cycle ergometer sprints, and 30 s Wingate test was conducted (Glaister et al, 2014;Woolf, Bidwell, Carlson, 2008). It seems that caffeine consumption in events that heavily rely on the glycolytic system (15 s to 3 min) has no positive impact on performance (possibly because of increase in plasma ammonia levels and decrease in intracellular pH) (Greer, McLean, Graham, 1998;Sökmen et al, 2008). Also, it is indicated that the sensitivity of caffeine consumers to the performance enhancing effects of caffeine is related to habitual intake (Woolf, Bidwell, Carlson, 2008).…”
mentioning
confidence: 99%
“…Somado a isso, a redução das concentrações plasmáticas de potássio (K + ) por meio do aumento da atividade da bomba de sódio e potássio (Na + /K + ATPase) no repouso (SIMMONDS et al, 2010) ou após o exercício (DOHERTY et al, 2002) podem proporcionar um ambiente favorável para o mecanismo de excitação-contração, melhorando o acoplamento das pontes cruzadas (LINDINGER et al, 1993). Por meio dos mecanismos descritos acima, pode-se prolongar (SIMMONDS et al, 2010) e/ou causar maior ativação (GREER et al, 1998) de unidades motoras durante este tipo de atividade.…”
Section: Discussionunclassified
“…Entretanto, a utilização da cafeína como recurso ergogênico em atividades de alta intensidade e curta duração, tem gerado ao longo dos últimos anos controvérsias a cerca da sua eficácia (ANSELME et al, 1992;BRUCE et al, 2000;COLLOMP et al, 1991;DOHERTY, 1998;GREER et al, 1998;JACKMAN et al, 1996;WILLIAMS et al, 1988;WYSS et al, 1986).…”
Section: Introductionunclassified